Reduced HSP70 expression under mild hypothermia is involved in bovine embryo growth suppression - Toshimichi ISHII; Sho NAKAMURA; Satoshi OHKURA; Shuichi MATSUYAMA (The Journal of Reproduction and Development, 2025)
Bovine blastocysts cultured under mild hypothermia (MH) can be maintained with non-hatching viable embryos compared to normothermic controls (38.5°C). However, the mechanism by which mildly hypothermic culture delays embryonic growth has not yet been elucidated. This study evaluated the number of cells in embryos cultured under MH conditions and the expression of genes involved in embryonic differentiation. Bovine blastocysts cultured under MH conditions exhibited reduced cell numbers and interferon-tau mRNA expression. Both forkhead box O3 (FOXO3) mRNA expression and FOXO3 protein level in blastocysts cultured under MH conditions were higher than those in normothermic controls (P < 0.05). On the phosphorylated FOXO3 protein level, there was no significant difference between blastocysts cultured under MH and normothermic conditions. In contrast, no significant difference was observed in the ATP content of blastocysts between the MH and normothermic groups. In blastocysts cultured under MH conditions, cold-inducible RNA-binding protein (CIRP) and RNA-binding motif protein 3 (RBM3) mRNA expression increased, and heat shock protein 70 (HSP70) mRNA expression decreased compared to that in normothermic controls (P < 0.05). Considering that HSP70 is involved in preventing apoptosis, these results suggest that MH retards embryonic development via apoptosis induced by HSP70 downregulation during the culture period.